2021
DOI: 10.1111/den.14015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultra‐low volume (≤1 L) bowel preparation fluids: Systematic review and meta‐analysis

Abstract: Background and Aims: High-quality bowel preparation is paramount for the diagnostic accuracy and safety of colonoscopy; however, it is often difficult for patients to adhere to high-volume laxatives, which may contribute to poor bowel preparation. This review aims to assess the efficacy of bowel preparation fluids of 1 L or less (≤1 L).Methods: We performed a systematic review including all relevant randomized controlled trials on ultra-low volume (≤1 L) bowel preparation fluids for colonoscopy published since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…As even a very high dose of PEG has limited efficacy, various composite PLG regimens have been developed, for example, PEG can be mixed with sodium ascorbate, sodium citrate, bisacodyl, or lactulose. These combined regimens are comparable to the 4L PEG regimen in terms of the efficacy of the bowel preparation and reduce the dosage of PEG 13–16 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As even a very high dose of PEG has limited efficacy, various composite PLG regimens have been developed, for example, PEG can be mixed with sodium ascorbate, sodium citrate, bisacodyl, or lactulose. These combined regimens are comparable to the 4L PEG regimen in terms of the efficacy of the bowel preparation and reduce the dosage of PEG 13–16 …”
Section: Discussionmentioning
confidence: 97%
“…These combined regimens are comparable to the 4L PEG regimen in terms of the efficacy of the bowel preparation and reduce the dosage of PEG. [13][14][15][16] Linaclotide is a novel, orally administered guanylate cyclase-C (GC-C) agonist that acts on intestinal epithelial cells. On the one hand, by activating GC-C/cyclic adenosine monophosphate (cAMP), it increases the phosphorylation level of protein kinase G-II (PKG-II), and by activating cystic fibrosis transmembrane conductance regulator (CFTR), it promotes the secretion of intestinal lumen liquid, softens feces, and increases the peristalsis of the stomach and intestine, thereby making defecation more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…In this nationwide Dutch prospective endoscopy database study, we In contrast to a recent meta-analysis, we showed that the ESGE quality standard requirement for adequate bowel preparation was also met with an ultra-low volume regimen. 14 The efficacy of ultra- 20 These conflicting results likely suggest that for adequate assessment of bowel preparation quality, a higher number of individuals need to be included. The CIR of 97.4% in Poland is on par with our study, while the ADR of 29.8% was lower in the Polish national screening program.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adequate patient instructions and lower volumes of bowel preparation increase patient compliance and willingness to repeat endoscopy 10,11 . However, reports on the effectiveness of ultra‐low volume bowel preparations pertaining to actual performance measures have suggested that they are not as effective as high‐ and low volume bowel preparations regimens 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…(Mahmood et al, 2018), but that is unavailable to change. So Increasing studies focus on improving bowel cleaning quality with some available strategies, including reinforcing patient education (Alvarez-Gonzalez et al, 2020;Kang et al, 2016), changing the type of laxative (Saito et al, 2021), the volume of laxative (Riswijk et al, 2021), preparation regimen(same-day dose/ split dose) (Barkun et al, 2020). Kim et al (2005) revealed that non-exercise was an independent risk factor of inadequate bowel preparation.…”
Section: Introductionmentioning
confidence: 99%